Memahami Konsep Penggilan Bagi Seorang Hamba Menurut Rasul Paulus Berdasarkan Surat 1 Korintus 9:16-19 - Hizkia Ananda Putirulan (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2023)
This article discusses the duties and rewards for a servant according to the apostle Paul in 1 Corinthians 9:16-19. The purpose of this study is to understand what are the duties and rewards of a servant according to Paul. In general, being a servant of God is often seen as a job that has no profit, because the wages earned are not much. This research was developed using the literature study method by collecting and reading journals, books and others that can help the author complete this paper properly. Then the results of this study state that being a servant is quite a difficult task, because being a servant of God is not only limited to preaching the truth of God's word. But also to provide an example of his life for every congregation of God as a roll model to be applied in their lives. The duty of a servant of God is to serve, because the service they do is a tangible manifestation of their faith in Christ. A servant of God must also be ready to leave their personal rights. And of course there is no ministry that runs without problems, and in facing problems there certainly needs to be sacrifice because, God will continue to take into account the sacrifice.